(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Age estimation is the most important parameter in clinical forensic medicine during human identification. Age estimation can be done from early physiological changes in the body, teeth development and radiological examina tion of ossification centers. Methodology & Results: This study was done on dead bodies which are brought for autopsy to the mortuary, Dept. AIIMS, New Delhi. A total of 70 patients were observed, out of which 41 were male and 29 are female. The ossification centers around Elbow joint completely fuse earliest at the age of 15 years, while in females, it is at 13 years. Complete fusion of proximal end of radius and ulna has occurred 2 years earlier in females, as compared to males. Conclusion: Total sample size for the study is not large enough, to make proper inferences regarding the ossification of joints. The Tanner-Whitehouse method and Greulich-Pyle method should be modified as applicable to the Indian pop ulation to make a more scientific assessment of the ossification status of joints.